Optimizing Social Media as a Means of Business Promotion - Agnes Yolanda; Ade Riska Nur; Ernawati; Ismi Azis (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2025)
E-commerce is a marketing or advertising medium that is very close to the target market. Society now depends on digital communication. This is an opportunity for the perpetrator businesses to make e-commerce a medium to attract consumer attention regarding the products you want to offer. This is the background for doing so Digital Marketing Research Accessories Business Development. Objective This research is to find out in depth about how strategies and digital management by the business actor. Research conducted using qualitative descriptive methods. The research data used is primary data obtained through in depth interviews with accessories business owners. The results of the research found that the accessories business carried out had experiencing developments in digital marketing, by continuing to strive for implementation from management, leadership and workplace digital skills.